A Comprehensive Review of Neuropsychologic Studies Supports the Concept That Adequate Folinic Acid Rescue Prevents Post Methotrexate Neurotoxicity. Issue 1 (12th January 2023) - Sadeh, Michelle; Toledano, Helen; Cohen, Ian J.
Abstract : Purpose: To review all studies providing evidence of the correlation between folinic acid (FA) rescue inadequacy and long-term cognitive damage in neuropsychological studies of children with acute lymphoblastic leukemia or osteogenic sarcoma treated under protocols using high-dose methotrexate and FA rescue. Methods: A comprehensive literature search was performed of all databases of the Web of Science Citation Index, during 1990–2020, for the terms: neuropsychological, neurocognitive, and cognitive, together with acute lymphoblastic (and lymphocytic) leukemia and osteogenic sarcoma. English-language peer-reviewed articles on neuropsychological assessments of children who had been treated with high-dose methotrexate without irradiation, and which included details of methotrexate and FA schedules, were selected. In addition, a personal database of over 500 reprints of articles from over 130 journals was reviewed on the subjects of methotrexate and FA and their side effects. Results: Three groups of studies were found and analyzed, with (1) no evidence of cognitive deterioration, (2) evidence of cognitive deterioration, and (3) more than 1 protocol grouped together, preventing separate analysis of any protocols, Protocols without cognitive deterioration reported adequate FA rescue, and those with cognitive deterioration reported inadequate FA rescue. Conclusion: Neuropsychological evaluation supported inadequate FA being the cause of neurocognitive damage after high-dose methotrexate and that adequate FA rescue prevents this complication.